Appications of Geomorphology to Forestry - Dhar, B. L.; Jha, M. N. (Indian Forester, 1977)
Incorporation of geomorphological observations to forestry has been stressed in this article. The current emphasis in the country either on afforestation or on the rational use of forest products. Due emphasis on Geomorphology can be of advantage in such activities.